Electropolymerized Poly(3,4‐ethylenedioxythiophene) Coatings on Porous Carbon Electrodes for Electrochemical Separation of Metals - Emre B. Boz; Marcell Fritz; Antoni Forner‐Cuenca (Advanced Materials Interfaces, 2023)
Abstract Electrode‐assisted techniques are well suited for the separation of ions from solutions with reduced energy and chemical consumption. This emerging platform can benefit greatly from the convection enhanced and zero‐gap reactor designs unlocked by macroporous electrodes, but immobilizing ion‐selective layers on such complex 3D architectures is challenging. Electropolymerization of conductive polymers is proposed as a coating methodology to fabricate highly conformal coatings with electrochemically switchable ion‐exchange functionality. To demonstrate this, the synthetic parameters, resulting morphology, and ionic separation performance of poly(3,4‐ethylenedioxythiophene) (PEDOT) on commercially available carbon paper electrodes are studied. Electropolymerization of PEDOT in organic solvents results in rougher morphologies with high sensitivity to electrochemical protocols employed. When polymerized in aqueous solutions of poly(4‐styrenesulfonate) (PSS−), the resulting PEDOT/PSS blend polymer forms smooth coatings with a controllable thickness down to 0.1 µm. With appropriate voltage bias, PEDOT/PSS coated electrodes can take up and release Ni2+ in the presence of excess Na+. Increasing the coating thickness decreases the adsorption capacity due to mass transfer limitations, and the maximum adsorption capacity for Ni2+ is reached for the thinnest coatings at 228 mg g−1. Through a systematic study of PEDOT/PSS coated carbon paper, electropolymerization is identified to be a promising avenue for porous electrode functionalization.